Improving the Ability to Memorize Daily Prayers through the Singing Method at ICCI GURKY NAMU TERASI Kindergarten - Hati, Surya (Jurnal Cendekia Islam Indonesia, 2025)
This Classroom Action Research aimed to improve the ability of young children at TK ICCI Gurky Namu Terasi to memorize daily prayers using the singing method. The research was conducted in two cycles, where the first cycle focused on introducing simple, repetitive songs to teach prayers, while the second cycle increased the frequency of singing activities and included additional strategies like visual aids and rewards. The results showed significant improvements in the children's ability to memorize and recite daily prayers. The use of music engaged the children, making the learning process enjoyable and effective. By incorporating melody and rhythm, the children were able to retain prayers more easily. Additionally, the social and emotional benefits of group singing were observed, as the children developed better communication skills and increased confidence. The study concluded that the singing method is an effective tool for teaching young children daily prayers, making the learning process more interactive, engaging, and memorable. The findings suggest that this approach can be applied to other areas of early childhood education to enhance learning outcomes.